Genetics of Strength and Power Characteristics in Children and Adolescents - Beunen, G.; Thomis, M.; Peeters, M.; Maes, H. H.; Claessens, A. L.; Vlietinck, R. (Pediatric Exercise Science, 2003)
The aim of this study is to quantify the genetic and environmental variation in isometric and explosive strength (power) in children and adolescents, using structural equation models. Arm pull (static strength) and vertical jump (explosive strength, power) were measured in 105 twin pairs from the Leuven Longitudinal Twin Study. Boys and girls were tested at annual intervals between 10 and 16 years and at l8 years. Path models were fitted to the observed strength characteristics and a gender heterogeneity analysis was performed at each age level. A model including additive genetic and specific environmental factors (AE-model) allowing for a difference in total phenotypic variance or in genetic/environmental variance components in boys and girls best explains both strength characteristics at most age levels. The additive genetic contribution for isometric strength varies between a2 = .44 and a2 = .83, and for explosive strength between a2 = .47 and a2 = .92, except at 16 years in males. In conclusion there is good evidence that during the growth period both static and explosive strength are under moderate to moderately strong genetic influence.